F. Nietzsche: The Principle Wille zur Macht - Mickevičius, Arūnas (Problemos, 2004)
The article deals with Nietzsche's philosophy as a radical critique of the classical thinking paradigm. Nietzsche used the will to power concept to separate himself from the dualism of classical thinking and especially from A. Schopenhauer's concept of the “will to live”, which leads to passivity. The category of “life” for Nietzsche does not mean inactive seclusion, but activity: possessing, subduing the weaker dominance of individual shapes, annexation. So the will to power was built on a dynamic, antagonistic foundation. The will to power in Nietzsche's thinking is not a “thing in itself”, as opposed to “phenomenon” (I. Kant), or else “a will” as opposed to “an image” (A. Schopenhauer). It is inseparable from its realisation, similarly as lightning is inseparable from its luminescence. The will to power decides upon an approach which allows no substance of “will” outside of phenomenon or existence of “an object in itself”; it is an approach that does not accept any “facts in themselves”, only interpretations. Therefore, Nietzsche's philosophy holds many associations with the postmodern paradigm that allows only an interpretative understanding of the world, i.e., understanding that creates only an interpretation of the interpretation. There is no absolute primordiality which would lend itself to interpretation, because anything can be the basis for interpretation. Therefore, “the will to power”, as non-substance, is inseparable from the basis of self-demonstration and, in the long run, is only an interpretation and an interpretation of the interpretation, i.e., a phenomenalistic understanding of the world. The essence of this phenomenalistic understanding is that “the world which we are capable of appropriating is only surface, generalized by oversimplified signs. It accepts only total appearance (Scheinbare). The will to power is inseparable from realisations which take place through the agency of two different types of forces: active and reactive. It indicates the difference between the forces and also is manifest in this “difference”. The will to power foresees not identity but difference, it shows, determines and manifests difference. With respect to the genesis of power or its generation, the will to power determines the relation between forces, but in its own tum is determined by the activity of these forces. It is at the same time both determined and determiner. Nietzschean “slave” and “master” moralities are based upon active and reactive forces. The active force is different from the reactive force in that in the active point we start with assertive and positive assumptions. Nietzsche created a theoretical construct based on the principle Wille zur Macht, where he emphatically praised “assertive” forces, and accused all classical thinking of turning away from life and associated it with reactive, negative forces. This construct is characterised by independently manifested speculative forms: genealogising, typology and symptomology. This means that every phenomenon we discuss springs from the will to power. Since it is determined by different forces, all phenomena are either associated with active or with reactive forces. In the long run, all typologically different phenomena must be determined according to symptoms. If the force is active, all phenomena related to it will be associated with symptoms of a full-blooded and healthy life. If the power is reactive, the phenomena associated with it will be related to symptoms of crisis, depression, weakness and sickness. These three forms of reasoning: genealogisation, typology and symptomatics that encompass the will to power and the construct, ultimately became known as semiology. This means that for Nietzsche, understanding the world is totally full of signs and totally interpretative. There are no “substances”, “essences”, “things in themselves”, etc.; there are only signs and their differentiated interpretations. This conception Nietzsche was named “perspectivism”. Therefore, Nietzsche's philosophy, based on the power of will, denies the exceptionally unique true opinion of the world and offers instead a variety of interpretations; foresees the possibility to look at the world through different eyes, i.e., determines a perspectivist approach to the world.
Keywords: metaphysics; genealogy; symptomology; typology; slave morality; master morality